PENGARUH JENIS TAYANGAN PROGRAM TELEVISI BAGI PERKEMBANGAN BUDI PEKERTI ANAK - yusuf sapari (JURNAL SIGNAL, 2015)
Theoretically there are at least three variables of main instruction: 1) condition of learning consist of objectives, barriers and characteristics of subject matter and student; 2) methods which consist of strategy of material organization (macro and micro), content delivery,and instruction management; 3) instructional performance which includs the effectiveness, efficiency and attractiveness of instruction. The instructional design development stages are (1) analysis of objective and subject matter charateristics; (2) Learning resources;(3) Student characteristic; (4) objectives and content of instruction; (5) strategy of content’s organization; (6)content delivery ; (7) instruction management;(8) development of evaluation procedure of instructional performance Student characteristic should become the base for selection and development of optimum instructional strategy. It is due to successful the implementation of the developed theory and principle of instruction. Relating to the moral degradation of youth, it’s necessary to develop optimum moral instruction strategy.In this case the instructional developer should base on the student characterictic, and moral development. There are six stages of moral development: (1) reward and punishment orientation;(2) instrumental orientation;(3) harmony orientation or good boy-nice girl; (4) ordered society; (5) contract social; (6) universal ethic. The information of student moral stages is important as it is the base of instruction program development, and Instructional media production.Keywords: Watch TV programs, Budi Character Development